Bibliometric analysis of research hotspots and emerging trends in mitophagy and atherosclerosis (2004–2024) - Ding, Shuchen; Zhang, He; Song, Luxia; Wang, Xinyi; Song, Lifang; Tian, Wende; Chen, Xuanye; Xu, Hao (Frontiers in Medicine, 2025)
BackgroundMitophagy is closely involved in the onset, progression and pathological mechanisms of atherosclerosis. This study set out to provide a comprehensive overview and identify emerging research trends in the field.MethodsA systematic literature retrieval was conducted across the Web of Science Core Collection (WoSCC) for publications spanning 2004 to 2024. Bibliometric analyses and knowledge mapping were performed utilizing CiteSpace, VOSviewer, R-Bibliometrix, Scimago Graphica and Excel to evaluate the intellectual landscape of the field.ResultsThe analysis reveals a fluctuating but overall increasing trend in annual publications. The United States and China are the primary contributors to the body of research, with leading institutions predominantly located in China, the United States, and Russia. Notably, the works of Orekhov AN stand out in terms of both quantity and quality. The most cited studies is Forrester SJ’s 2018 publication in Circulation Research. Additionally, keyword analysis highlights the prevailing research hotspots, including: (1) key molecules such as NF κB, NLRP3 inflammasome, and mitochondrial DNA; (2) critical pathological processes such as oxidative stress, mitochondrial dysfunction, and mitochondrial dynamics; and (3) and the role of mitophagy within vascular smooth muscle cells, endothelial cells, and macrophages in the pathogenesis of atherosclerosis.ConclusionThe study of mitophagy in atherosclerosis has garnered increasing attention, with substantial progress made in understanding its molecular and cellular mechanisms. This work highlights the current research hotspots and identifies prospective directions for future exploration. Further investigation into the intricate mechanisms governing mitophagy may uncover novel therapeutic strategies that could mitigate the progression of atherosclerosis.